The tenets of cognitive existentialism - Ginev, Dimitŭr (Series in Continental thought, 2011)
In The Tenets of Cognitive Existentialism, Dimitri Ginev draws on developments in hermeneutic phenomenology and other programs in hermeneutic philosophy to inform an interpretative approach to scientific practices. At stake is the question of whether it is possible to integrate forms of reflection upon the ontological difference in the cognitive structure of scientific research. A positive answer would have implied a proof that (pace Heidegger) "science is able to think." This book is an extended version of such a proof. Against those who claim that modern science.